2008
DOI: 10.1016/j.fertnstert.2007.02.016
|View full text |Cite
|
Sign up to set email alerts
|

The combined effect of age and basal follicle-stimulating hormone on the cost of a live birth at assisted reproductive technology

Abstract: Objective-To predict the cost of a delivery following assisted reproductive technologies (ART).Design-Cost analysis based on retrospective chart analysis. Setting-University-based ART programPatients-Women aged ≥26 and ≤42 years with FSH levels ≤ 12 IU/L on day 3 undergoing a first cycle of fresh, non-donor ART.Interventions-Logit regression using a fractional polynomial model of age and basal FSH was used to estimate the probability of a live birth. Cost analysis was applied to the resulting prediction.Main o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 25 publications
(29 reference statements)
0
6
0
Order By: Relevance
“…This equals 20-fold to 90-fold the gross national income per capita of U.S.$4940 for the year 2006 in Egypt (33). Henne et al (34) have shown that, in the United States at a live-birth rate <5%, the cost of ART is high and greatly exceeds the cost of donor cycles. The cost rose exponentially at lower probabilities of live birth.…”
Section: Discussionmentioning
confidence: 99%
“…This equals 20-fold to 90-fold the gross national income per capita of U.S.$4940 for the year 2006 in Egypt (33). Henne et al (34) have shown that, in the United States at a live-birth rate <5%, the cost of ART is high and greatly exceeds the cost of donor cycles. The cost rose exponentially at lower probabilities of live birth.…”
Section: Discussionmentioning
confidence: 99%
“…Some ART clinics have chosen to abandon any screening and proceed to stimulate all candidates using a 'proof-in-the-pudding' type of logic (16). Of course, this practice leads to high cancellation rates, or oocyte retrieval for patients for whom live birth rates are expected to less than 5%, at great cost to patients (31). Therefore, a more cost-effective approach is certainly warranted.…”
Section: A Solution To the Problem Of Ovarian Insufficiency Screeningmentioning
confidence: 99%
“…There are significant consequences associated with the diagnosis, such as reduction in pregnancy rate, increased miscarriage rate (6)(7)(8)(9)(10)(11)34), and increased cost per delivery (31,(35)(36)(37).…”
Section: Should Screening Tests For Ovarian Insufficiency Be Abandoned?mentioning
confidence: 99%
See 1 more Smart Citation
“…Although studies have examined the cost of IVF in the United States (24), including the influence of state-mandated insurance coverage on utilization (5, 6) as well as the impact of age and/or basal FSH levels (7, 8), to the best of our knowledge the only qualitative research addressing IVF patients’ attitudes toward costs and insurance has been in the United Kingdom. Peddie et al (9) performed semistructured interviews with 25 women who had decided to end treatment after unsuccessful IVF treatment, and Redshaw et al (10) analyzed the open-ended written responses to a mailed questionnaire of 108 women who had conceived after IVF.…”
mentioning
confidence: 99%